Stakeholder Pressure and Its Effect on Sustainability Report - Indah Fajarini Sri Wahyuningrum; Muhammad Ihlashul’amal; Retnoningrum Hidayah; Fitrarena Widhi Rizkyana (Universitas Diponegoro, 2023)
The quality of corporate sustainability reports in Indonesia is unfortunately found to be lacking, with a rating of only 53.6%. This is significantly lower compared to the average of other Southeast Asian countries. However, stakeholders are becoming more aware of their role in encouraging public companies to disclose sustainability information. This study intends to look at the quality of sustainability reports released by Indonesian public firms, as well as the impact of stakeholder pressure on these reports' quality. Data from annual and sustainability reports of businesses listed on the Indonesia Stock Exchange between 2016 and 2020 are used in the research, which is based on GRI's G4 guidelines and the GRI Standards 2016. The study looks at numerous stakeholder pressures, including pressure from creditors, media exposure, the Big Four accounting firms, employees, consumers, environmentally sensitive industries, and shareholders. The results show that companies with significant media coverage typically produce sustainability reports of high quality. However, pressure from other stakeholders has not been found to have a significant impact on the quality of these reports. This study provides valuable insights into the state of sustainability reporting in Indonesia and aims to encourage stakeholders to actively participate in promoting a sustainable industry.